An efficient method for assembling layered g-C3N4 nanosheets grow on 1D pore channels carbon fibers as a composite photocatalyst by ultrasound-assisted exfoliation and hydrothermal method. (December 2016) - Ma, Tengfei; Bai, Jie; Liang, Haiou; Wang, Junzhong; Li, Chunping
Abstract: A composite catalyst that layered graphite carbon nitride (g-C3 N4 ) nanosheets adhered on electrospun carbon fibers (CFs) carrier was prepared, and this catalyst occupied the efficient photocatalytic activity. The carbon fiber was obtained through electrospinning technology and high-temperature calcination process. The layered g-C3 N4 nanosheets was derived through the direct heating and ultrasonic exfoliation. After that, the g-C3 N4 /CFs were successfully synthesized in the hydrothermal process. In the process of degradation, composites had the capacity of degradation to different organic dyes under the UV-light irradiation, meanwhile, catalyst had excellent capacity of adsorption and a certain recycling performance. Thus, g-C3 N4 /CFs catalyst has potential appliance value in the degradation of organic pollutants. Highlights: Layered g-C3 N4 nanosheets grown on CNFs carrier to form g-C3 N4 /CNFs, which was prepared successfully. The g-C3 N4 /CNFs can be easily used in the next reaction because of the existence of CNFs membrane. The g-C3 N4 is presented in layer could adhere on CNFs tightly to carry out the cyclic reactions. The g-C3 N4 /CNFs exhibited excellent adsorption performance and photocatalytic activity to various organic dyes.